A Representasi Pesan Moral Dalam Film Luqothoh Karya Rumah Produksi Tebuireng - Atika Suri, Putri Sukma; Anwari (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Abstract : Basically, a film is a work of art that is born from the role of actors in playing their characters. One example is the film Luqothoh by the Tebuireng Production House, which was produced by Abdullah Aminuddin Aziz. This film tells the story of Kaf (played by M. Dzannuroin Aldivano), the great-grandson of KH. Hasyim Asy'ari, who spent his time as a santri, was filled with trials and tribulations that made him mature. In this research, the researcher formulated two main problems that will be answered in this thesis, namely: (1) What are the denotative, connotative and mythical meanings of the scenes that convey moral messages in the film Luqothoh? (2) What is the moral message implied in the film Luqothoh? To answer these two problems, the researcher used a descriptive qualitative approach by applying a semiotic analysis method based on Roland Barthes' theory. The results of this analysis show that there is a moral message that includes values such as: respecting teachers, upholding honesty and responsibility, having empathy, holding commitment in fulfilling promises, having a trustworthy nature, appreciating the help given, carrying out devotion to worship, being wise in making decisions. , have firmness in your stance, and try seriously. Keywords: Morals, Semiotics, Luqothoh Film